Nghiên cứu tác dụng của hướng sinh dục nam của cao ba kích trên thực nghiệm / Nguyễn Thị Liên, [... và những người khác] - Trần, Thị Thu Trang
The dry ethanol extracts of Ba kich (Morinda oﬁicinalis How) as a traditional medicine especially for men to improve the genre! heath and vitality was experimentally investigated for androgenic effects in mice. Repeated oral administration of the extracts (200 mg/kg. p.o.) signiﬁcantly increased plasma testosteron levels and the weight ofthe male sexual organ including the seminal vesicle, Cowper's glands and evator ani-bulbocavemosus muscle. but the weight ofthe testicle remained unchanged signiﬁcantly. In addition, 15-day administration course ofthe tested extracts per se did not inﬂuence the body weight in mice. These provided evidences for the androgenic effects and usefulness for supporting physiological function in men of the Ba kich dry extracts.